Um desafio para a regulação do mercado de assistência à saúde no Brasil: a escolha do consumidor de planos de saúde - Alcoforado, Flávio Carneiro Guedes (2003)
The objective of this dissertation is to discover and to analyze the way how the consumer uses his/her perception to decide contracting a health plan, to supply elements that can serve to subsidize the State, the market and the consumers, in relation to the knowledge on the process of choice of the consumer and the decisions of purchase and contracting services of private health. The estimated one is to evidence that the brand of health plan is an important variable and decisive to the consumer contracting the service of a company that operates in these sector, because mean for the consumer security about the product, through the symbolism that the same one represents, despite the consumer not knowing to the certainty what is contracting in quality and amount. The theoretical construction is carried through using literature of anthropology of the consumption, theory of modernity, theory of the regulation, economic utilitarism, and marketing. Moreover, referential specific theoretician on the regulation of the market of health plans in Brazil. The health plan market in Brazil is anti-symmetrical and the consumer doesn¿t have knowledge technician who makes possible it to form judgment and to carry through rationality choices. Than the consumer uses to his/her decision symbolic elements that are available to his/her and supply to his/her the security that is look likes in the consumption of this kind of good. These symbolic elements related the confidence and security and are into the strong brands of the companies and are transmitted to the consumer through the mass media. In this dissertation are used as sources of data some information of the regulatory agency of the sector ¿ ANS -, a research of public opinion with health plans users and the results of the application of proper questionnaires for this research.